Impact of Gastrointestinal In Vitro Digestion and Deficit Irrigation on Antioxidant Activity and Phenolic Content Bioaccessibility of “Manzanilla” Table Olives - Lucía Sánchez-Rodríguez; Marina Cano-Lamadrid; Ángel A. Carbonell-Barrachina; Francisca Hernández; Esther Sendra (Journal of Food Quality)
This was the first study investigating the polyphenol content, antioxidant potential, and polyphenol bioaccessibility after in vitro digestion of table olives grown using regulated deficit irrigation (RDI) treatments to save irrigation water. Two experiments were carried out: (i) experiment A, where RDI was applied during the pit hardening stage and (ii) experiment B, where RDI was applied during the rehydration stage. Only slight differences among irrigation treatments were observed in two antioxidant assays (ABTS+• and DPPH•) and on TPC for the soluble fraction after in vitro digestion. An average of 1 g gallic acid equivalents kg−1 of table olives were found after digestion. Approximately, 12% of the polyphenols of table olives were bioaccessible for human absorption. Saving water techniques influence neither the final polyphenol content and antioxidant potential of table olives nor the bioaccessibility of polyphenols. The consumption of 40 g of table olives will provide 40 mg of bioaccessible polyphenols able to provide associated health benefits (∼7% of the daily polyphenols intake recommendation).